The relationship between posttraumatic growth and health-related quality of life in adult cancer survivors: a systematic review - Liu, Zhunzhun; Doege, Daniela; Thong, Melissa S. Y.; Arndt, Volker (Journal of affective disorders, 2020)
Background - Studies have reported mixed findings on the relationship between posttraumatic growth (PTG) and health-related quality of life (HRQOL) in cancer survivors. This review aims to give an overview of these studies and to identify potential study- and sample-level factors that could contribute to the heterogeneity of those findings on the relationship between PTG and HRQOL in cancer survivors. - Methods - Multiple electronic databases were systematically searched using the concepts ‘posttraumatic growth’, ‘cancer’, and ‘health-related quality of life’. Eligible studies (published until 2018) were reviewed, quality-assessed, and effect sizes were extracted and synthesized. - Results - Of the 37 included articles, 22 received a rating of ‘weak’, 11 ‘moderate’ and 4 ‘strong’ in study quality assessment. The overall sample comprised 7954 individuals, mean age of 55.30 years, >50% females, predominantly breast cancer, and survivors mainly within 5 years post-diagnosis. The synthesized results revealed a positive association between PTG and HRQOL (Fisher's z= 0.16) on a total scale, with significant high heterogeneity (I2=75%). Variations in HRQOL measurement and methodological inconsistency contributed to study-level differences of effect sizes. Sample-level characteristics such as geographic region, smaller sample sizes (n < 100) and so on contributed to heterogeneity. - Limitations - Studies assessing the relationship between PTG and HRQOL were heterogeneous, of weak study quality generally, and results were difficult to combine. - Conclusions - Most studies found a positive relationship between the factors suggesting that PTG may play a role for successful coping following cancer. However, studies of higher quality and longitudinal design are needed.